Pola Aktivitas Orangutan (Pongo abelii) di Kawasan Taman Nasional Gunung Leuser Ketambe Aceh Tenggara - Afkar ,; Nadia Aldyza (Biotik, 2015)
The study was conducted in the area of Gunung Leuser National Park Ketambe, Southeast Aceh, in January 2016. This study aimed (1) to find out the activity patterns of orangutan (Pongo abelii), and (2) to determine the dominant activities of orangutan (Pongo abelii) in Gunung Leuser National Parks Ketambe Southeast Aceh district. The data were collected by using Focal Animal Sampling Method and recording of data using One Zero Sampling Method. The research found that there were three orangutans (Pongo abelii), and the activities of orangutan (Pongo abelii) were eating 13 % , moving 4 % , sitting 21 % , standing 5 % , sleeping 0 % , looking for lice 4 % , swinging 7 %, hanging in tree 21 % , playing 0 % , feeding 25 %, breast-feeding and rolling 0 % 0 %. Based on these activities, the most dominant activity carried out by Pongo abelii in the Gunung Leuser National Park Ketambe Southeast Aceh Regency was foraging.